Prevalence and Risk Factors of Scabies in Tando Muhammad Khan, Sindh: A Retrospective Study - Shaikh, Marvi; Memon, Maleeha; Qureshi, Muhammad Yasir; Qazi, Sumayya; Ismail, Bisma; kashif, Mehnaz (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To assess the prevalence and risk factors associated with scabies in Tando Muhammad Khan, Sindh, Pakistan. METHODOLOGY: A retrospective observational study was conducted at the dermatology outpatient clinic of Indus Medical College and Hospital, reviewing medical records from January to August 2024. A total of 300 patients' records were examined for documented cases of scabies based on physical assessments. Sociodemographic and dietary data were extracted from existing medical records and hospital databases. The collected data were then analyzed using SPSS, with the results presented in tables and graphs. RESULTS: Among the 300 scabies cases, 49.1% were adult males, 32.3% were adult females, and 9.3% were teenagers and children. Adult males showed the highest Prevalence, with many cases linked to lower socioeconomic backgrounds. The mean Age for male patients was 42.71 years, and 53.3% were Sindhi. Most patients (86%) relied on surface water, and 81% were non-vegetarians. Crusted lesions were the most common, with 97% of patients exhibiting multiple lesions across various body areas. CONCLUSION: The study reveals that overcrowding, poor hygiene, and limited access to clean water are major risk factors. Public health interventions focusing on hygiene education and better water access are crucial to reducing scabies in the region.